A novel approach for the detection of early gastric cancer: Fluorescence spectroscopy of gastric juice. Issue 6 (25th April 2013) - Deng, Kai; Zhou, Li Ya; Lin, San Ren; Li, Yuan; Chen, Mo; Geng, Qiu Ming; Li, Yu Wen
<x xml:space="preserve">Abstract</x> Objective This study aimed to investigate the efficacy of fluorescence spectroscopy of gastric juice for early gastric cancer (EGC) screening. Methods Gastric juice was collected from 101 participants who underwent endoscopy in the Outpatient Endoscopy Center of Peking University Third Hospital. The participants were divided into three groups: the normal mucosa or chronic non‐atrophic gastritis (NM‐CNAG) group (n = 35), advanced gastric cancer (AGC) group (n = 33) and EGC group (n = 33). Fluorescence spectroscopic analysis was performed in all the gastric juice samples and the maximum fluorescence intensity of the first peak (P1FI) was measured. Results The mean fluorescence intensity of P1FI of gastric juice in AGC (92.1 ± 10.7) and EGC (90.8 ± 12.0) groups was significantly higher than that in the NM‐CNAG group (55.7 ± 7.5) (AGC vs NM‐CNAG, P = 0.006 and EGC vs NM‐CNAG, P = 0.015, respectively). The areas under the receiver operating characteristic curves for the detection of AGC and EGC were 0.681 (95% confidence interval [CI] 0.553–0.810, P = 0.010) and 0.655 (95% CI 0.522–0.787, P = 0.028). With the P1FI of ≥47.7, the sensitivity, specificity and accuracy for detecting EGC were 69.7%, 57.1% and 63.2%, respectively. Conclusions The enhancement of P1FI of gastric juice occurs at the early stage of gastric cancer. Fluorescence spectroscopy of gastric juice may be used as a novel screening tool for the early detection of gastric cancer.